Adverse events in patients with advanced urothelial carcinoma treated with erdafitinib: a retrospective pharmacovigilance study - Yuan, Tengfei; Li, Faping; Hou, Yuchuan; Guo, Hui (Frontiers in Pharmacology, 2023)
On April 12, 2019, erdafitinib gained the first FDA approval as the second-line treatment for adult patients with locally advanced or metastatic urothelial cancer following progression during or after at least one previous line of platinum-based chemotherapy. However, the long-term safety profile of erdafitinib in a large patient population remains unexplored. The current study aimed to assess the adverse events (AEs) associated with erdafitinib through data mining of the US Food and Drug Administration Adverse Event Reporting System (FAERS). Method: The reporting odds ratio (ROR), the proportional reporting ratio (PRR), the Bayesian confidence propagation neural network (BCPNN), and the multi-item gamma Poisson shrinker (MGPS) algorithms based on disproportionality were employed to quantify the signals of erdafitinib-associated AEs. Results: A total of 6,322,279 reports of AEs were retrieved from the FAERS database spanning 2019 to 2022, out of which, 700 reports of erdafitinib as the "primary suspected" were identified. These erdafitinibinduced AEs were observed across 24 targeted system organ classes (SOCs). After conforming to the four algorithms at the same time, a total of 441 signals of erdafitinib-induced AEs were detected across 23 SOCs. Notably, signals associated with metabolism and nutrition disorders, eye disorders, and skin and subcutaneous tissue disorders were among the most prevalent. The median onset time for AEs was found to be 54 days (interquartile range [IQR] 17-112 days), with a majority of AEs occurring within the initial 6 months after initiating erdafitinib (37.23% within the first month, 15.53% within the second month, and 16.79% within the third month).The findings of this study align with existing clinical observations, offering a comprehensive long-term post-marketing safety evaluation of erdafitinib. The results provide valuable evidence to enhance the understanding of erdafitinib's safety profile, aiding further research and guiding clinical practice.